Skin disorders that mimic melanoma: a review - Irmadita Citrashanty; Made Putri Hendaria (Explorer Front, 2025)
Malignant melanoma is a skin disorder that originates from the degeneration of melanocyte pigment cells towards malignancy, which is characterized by an increasingly enlarged and irregular and more prominent color change. Many skin disorders have similarities with malignant melanoma, which sometimes makes it difficult for medical personnel to make a diagnosis. Skin conditions that resemble melanoma are categorized into histogenetic lines such as melanocytic (Spitz naevus, Cellular blue naevus, melanocytic naevus with focal atypical epithelioid component/clonal naevus, Deep penetrating naevus), neural (Malignant peripheral nerve sheath tumor, Neurotheceomakell (Sicatrical). When the intraepidermal melanocytic component is subtle or missing, or the tumor displays uncommon histological features, misclassification of melanoma is more likely. The recent implementation of clearer clinical and histopathological criteria with the development of dermoscopy and computer technology has been able to led to the early detection of melanoma, which has contributed to the increased diagnosis of this disease and other skin diseases that may have similarities to melanoma. This review aimed to differentiate melanoma-like skin disorders.